A Simplified Approach for Two-Dimensional Optimal Controlled Sampling Designs. (25th May 2014) - Tiwari, Neeraj; Chilwal, Akhil
Abstract : Controlled sampling is a unique method of sample selection that minimizes the probability of selecting nondesirable combinations of units. Extending the concept of linear programming with an effective distance measure, we propose a simple method for two-dimensional optimal controlled selection that ensures zero probability to nondesired samples. Alternative estimators for population total and its variance have also been suggested. Some numerical examples have been considered to demonstrate the utility of the proposed procedure in comparison to the existing procedures.